Assessing the authenticity and purity of a commercial Bacillus thuringiensis bioinsecticide through whole genome sequencing and metagenomics approaches - Van Laere, Yari; Fraiture, Marie-Alice; Gobbo, Andrea; De Keersmaecker, Sigrid C. J.; Marchal, Kathleen; Roosens, Nancy H. C.; Vanneste, Kevin (Frontiers in Microbiology, 2025)
Biopesticides, biological agents for pest control in plants, are becoming increasingly prevalent in agricultural practices. However, no established methodology currently exists to assess their quality, and there are currently no publicly available authenticity and purity evaluations of commercial products. This lack of data may represent risks because of their widespread dispersal in the environment. We evaluated the potential of whole genome sequencing (WGS) and metagenomics approaches, including nanopore long-read sequencing, to verify both authenticity (i.e., the labeled strain) and biological purity (i.e., the absence of any undesired genetic material) of commercial Bacillus thuringiensis bioinsecticides. Four commercially available bioinsecticidal products containing Bacillus thuringiensis serovar kurstaki strain HD-1 were collected from the European market as a case study. Two sequencing approaches were employed: WGS of isolates and metagenomics sequencing of all genetic material in a product. To assess authenticity, isolate WGS data were compared against the publicly available reference genome of the expected strain. Antimicrobial resistance gene content, insecticidal gene content, and single nucleotide polymorphism differences were characterized to evaluate similarity to the reference genome. To assess purity, metagenomic sequencing data were analyzed using read classification and strain differentiation methods. Additionally, long- and short-read data were used to assess potential large-scale structural variations. Our results confirmed all investigated products to be authentic and pure. With the increasing usage of biopesticides, it is crucial to have adequate quality control methods. Our proposed approach could be adapted for other biopesticides, and similar products, providing a standardized and robust approach to contribute to biopesticide safety.